Green Synthesis of Silver Nanoparticle from Brassica Oleracea for Determination of Paracetamol in the Presence of Tyrosine, Leucine and Alanine by Derivative Method - Muhammad Ismail, Wang Xiangke, Saima (Pakistan Journal of Medical & Health Sciences, 2023)
In this work, biogenic silver nanoparticles (Ag NPs) from Brassica oleracea (Bo) leaf extract (AgNP-Bo) were prepared and utilized in synthetic mixtures for the accurate, effective, and sensitive spectrophotometric detection of Paracetamol. Measurements in the UV-Visible, X-ray diffraction (XRD), and scanning electron microscopy (SEM) have been used to confirm the synthesis of AgNP-Bo. These statistics indicate that the average particle size is 26.39 nm, the crystallinity has an aggregated structure, and the typical absorption wavelength is 445 nm. To decrease the possible influence of the listed water-soluble interference analytes, namely Tyrosine, Alanine, and Leucine, the 2nd order derivative method was used for our investigation. Using complexation with AgNP-Bo, the linear range, limit of detection (LOD), and relative standard deviation (RSD) for Paracetamol were calculated. The obtained values were 0.1-2, 0.09 µM, and 1.06%, respectively. With average percent recovery values of 93.33, 96.67, and 90.00%, respectively, AgNP-Bo also demonstrated excellent performance for Paracetamol detection in synthetic combinations including Tyrosine, Alanine, and Leucine. The suggested technique applied effectively for the quantitative analysis of synthetic mixtures, which makes it possible to employ Ag NPs going forward to determine biological molecules when interfering analytes from actual samples are present. Keywords: Silver nanoparticles; Brassica oleracea; Paracetamol; 2nd order derivative spectrophotometry; Interferences.